2000
DOI: 10.1017/s1357729800054928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incremental changes in forage: concentrate ratio on plasma hormone and metabolite concentrations and products of rumen fermentation in fattening beef steers

Abstract: As part of an investigation of factors responsible for a previously reported lower efficiency of carcass lean gain in steers offered grass silage diets, 16 Simmental × Friesian steers (515 (s.e. 6·4) kg) were offered perennial ryegrass silage ad libitum (C0) or silage plus rolled barley at 200 (C20), 400 (C40) or 600 (C60) g/kg total diet dry matter (DM). Barley-supplemented diets were intake-restricted to provide equal DM and metabolizable energy (ME) intakes to those offered C0. Eight steers were selected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
15
1
Order By: Relevance
“…Mechanisms that control the deposition of lean and fat include the pancreatic hormones (insulin and glucagon) and the hormones of the somatotrophic axis (GH and IGF-1). Thorp et al (2000) investigated the effects of forage-to-concentrate ratio, fed as equal digestible energies, on the circulating concentrations of insulin, IGF-1, glucagon and blood metabolites in growing beef steers. They reported increases in insulin and IGF-1 concentrations in addition to increases in plasma concentrations of the metabolites b-hydroxybutyrate and urea with increasing concentrate-to-forage ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms that control the deposition of lean and fat include the pancreatic hormones (insulin and glucagon) and the hormones of the somatotrophic axis (GH and IGF-1). Thorp et al (2000) investigated the effects of forage-to-concentrate ratio, fed as equal digestible energies, on the circulating concentrations of insulin, IGF-1, glucagon and blood metabolites in growing beef steers. They reported increases in insulin and IGF-1 concentrations in addition to increases in plasma concentrations of the metabolites b-hydroxybutyrate and urea with increasing concentrate-to-forage ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Thus in the present experiment (380 g starch/kg dietary dry matter (DM)) and in Sutton et al (1988) (380 g starch/kg DM, estimated from ingredient composition) and Thorp et al (2000) (340 g starch/kg DM, estimated) postprandial increases in plasma insulin and glucagon were observed when diets were fed twice daily. However, increasing the number of feeds (present experiment two to four times daily; Sutton et al, 1988, two to six times daily) or reducing the proportion of starch in the diet (present experiment; Sutton et al, 1988;Thorp et al, 2000) attenuated the response. Thus it seems necessary to exceed both a threshold in the amount of starch consumed per feed and proportion of starch in the total amount of feed consumed to increase propionate concentration rapidly enough to generate post-prandial peaks in insulin and glucagon.…”
Section: Discussionmentioning
confidence: 47%
“…Smith et al (2006) have shown that post-prandial increases in plasma insulin and glucagon concentration are related specifically to propionate absorption from the rumen into the portal circulation. Propionate production in the rumen is related to starch digestion and thus the extent of increases in plasma insulin and glucagon concentration is related to the proportion of starch in the diet (Thorp et al, 2000). However, changes in peripheral insulin and glucagon concentration in response to changes in the numbers of meals fed daily have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies provided evidence that IGF-I stimulated the growth of rumen epithelial cells in vitro (Baldwin, 1999). Both energy (Thissen et al, 1994) and protein (Thorp et al, 2000) intakes have marked effects on plasma IGF-I concentration and IGF-I mRNA abundance in sheep (Pell et al, 1993;Hua et al, 1995), heifers (Nosbush et al, 1996), beef steers (Thorp et al, 2000), bulls (Renaville et al, 2000), and calves (Smith et al, 2002). Feed intake and nutritional status are considered to be the main factors affecting IGF-I status in mammals (Thissen et al, 1994;Ketelslegers et al, 1995).…”
Section: The Igf-i Concentration and Igf-i Mrna In Tissuesmentioning
confidence: 99%